PERANCANGAN APLIKASI TATA KELOLA KEUANGAN SALON YINHOA BERBASIS WEB - Marzelino, Kevin (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
Prior to the creation of this web-based financial management application, Salon Yinhoa ​​carried out all financial processes using the traditional method with on-the-spot transaction processes and recording was done manually using an excel file. As customers increase, recording transactions is considered to be quite time-consuming and a solution is needed to simplify financial management. Therefore, it is necessary to design a web-based financial management application for Salon Yinhao as a database for financial management using the SDLC-waterfall method. The final result is that the web-based application is used to facilitate financial management at Salon Yinhoa.